Mutation and Career Development to the Performance of Structural Officials (Case Study of Karawang Government) - Neneng Sofiyanti; Dian Hakip Nurdiansyah (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2017)
Mutation and career development in Karawang Municipality is implemented in the hope to improve the performance of its employee. The purpose of this research wash to determine, review and analysis how much the effect of mutation and career development partially and simultaneously to the Performance of Echelon Structural Officer IV in the Governement of Karawang Municipality. The number of samples were 250 people, with the sampling technique of Proportionate Stratified Random Sampling and data was analyzed by using descriptive and verificative methods (Path Analysis). The research results indicates that descriptively, mutationis responded as strongly agree and agree in accordance with each indicator of purpose. The implementation of career development is responded as strongly agree and agree in accordance with the indicator of interest and satisfaction.The performance of official is responded as well for all indicators of the fulfillment of all necessary resources. Verificatively, the direct partial effect between mutation and official performance is on a low scare (R = 0.215) while the indirect effect is on a very low scale (R = 0.196). In the hypothesis testing, it was discovered that there is a significant relationship. Keywords: Mutation, Career Development, Performance